A Comparison of the Economic Thought of Adam Smith and Al-Ghazali and Its Adaptation to the Creative Economy in Indonesia - Wahid Mustafa Zain; Sochimin Sochimin (Al-Sharf: Jurnal Ekonomi Islam, 2026)
This study aims to compare Adam Smith's classical economic thinking with al-Ghazali's Islamic economic thinking and its acclimatization with the creative economy in Indonesia. The research methodology uses library research. The results of the research provide an explanation of Adam Smith's thoughts on the essence of human greed, the free market mechanism, the invisible hand, value theory, division of labor, and welfare. In contrast, al-Ghazali's thoughts focus on the concepts of mashlahah, voluntary exchange and market evolution, production activities, the urgency of zakat and the prohibition of usury, barter and the evolution of money, to the capacity of the state and public finance. Al-Ghazali's thoughts are adapted to the situation and conditions of the creative economy in Indonesia. The global and Indonesian creative industries contribute to growth but also face challenges. The implications of this research emphasize that the principles put forward by al-Ghazali can be practiced in the context of the creative economy and free it from the classical economic system that hinders the creative industry.